\[ \begin{array}{l} \text { (10) } x^{2}-4 x y-x+4 y=0 \\ x+2 y-3=0 \end{array} \]
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
Let’s solve the system of equations given: 1. The first equation is \(x^{2} - 4xy - x + 4y = 0\). 2. The second equation is \(x + 2y - 3 = 0\), which can be rearranged to express \(x\) in terms of \(y\): \[ x = 3 - 2y \] Now, substitute this expression for \(x\) into the first equation: \[ (3 - 2y)^{2} - 4(3 - 2y)y - (3 - 2y) + 4y = 0 \] Expanding \( (3 - 2y)^{2} \): \[ (3 - 2y)^{2} = 9 - 12y + 4y^{2} \] And substituting into the equation: \[ 9 - 12y + 4y^{2} - 4(3y - 2y^{2}) - (3 - 2y) + 4y = 0 \] Now simplify: \[ 9 - 12y + 4y^{2} - (12y - 8y^{2}) - 3 + 2y + 4y = 0 \] Combine like terms: \[ 9 - 3 + 4y^{2} + 8y^{2} - 12y + 2y + 4y = 0 \] \[ 6 + 12y^{2} - 6y = 0 \] Now set the equation to 0: \[ 12y^{2} - 6y + 6 = 0 \] Divide through by 6 to simplify: \[ 2y^{2} - y + 1 = 0 \] Now we can use the quadratic formula \(y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\): Here, \(a = 2\), \(b = -1\), and \(c = 1\): \[ b^2 - 4ac = (-1)^{2} - 4 \cdot 2 \cdot 1 = 1 - 8 = -7 \] Since the discriminant is negative, it means that there are no real solutions for \(y\). Therefore, there will also be no real solutions for \(x\). So the system has no real solutions! 🎉